Evaluation of the Evacuation of Essential Buildings: Interaction of Structural and Human Behaviour through Nonlinear Time-History Analysis and Agent-Based Modelling - Delgado, M. (2020)
In this article, a performance assessment of the evacuation system is established for educational buildings. Structural and geotechnical information of the building is collected and introduced into a database. A similar procedure was realized for the information related to the occupants. Using this information, a) the structural fragility and localized collapse were determined and b) the interaction of the person with the partial collapse was established. For the first aspect, nonlinear time history was used, and for the second, the agent-based modeling was applied to recreate the reaction of people that face the micro collapse. Therefore, the important results of this evaluation are: 1) To localize collapsed beans and columns that make inoperable evacuation routes, 2) to localize bottleneck areas that people concentration during evacuation, and 3) quantification of affected people, in terms of persons caught up in the building that cannot evacuate.